2021
DOI: 10.3390/ijerph18084275
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality of Life in Infertility Treated Women in Poland

Abstract: The aim of this study was to assess the quality of life (QoL) of infertility treated women as it can affect the effectiveness of therapy. This cross-sectional study was conducted with Abbreviated World Health Organization Quality of Life questionnaire (WHOQOL-BREF), Fertility Quality of Life tool (FertiQoL) and an author’s questionnaire. The study included 1200 women treated for infertility without the use of assisted reproductive technology (non-ART), intrauterine insemination (IUI), or in vitro fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
2
19
1
1
Order By: Relevance
“…A significant difference between the study groups and the control group was found in the Environment domain. This relationship was not noted between the examined women [ 17 ]. Bolsoy et al also reported that in the Environment domain there occurred similar differences in the presented results between men and women [ 21 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A significant difference between the study groups and the control group was found in the Environment domain. This relationship was not noted between the examined women [ 17 ]. Bolsoy et al also reported that in the Environment domain there occurred similar differences in the presented results between men and women [ 21 ].…”
Section: Discussionmentioning
confidence: 97%
“…This publication is the second part of the study on the quality of life of patients treated for infertility in Poland [ 17 ]. In the first part, we the quality of life of women, and compared QoL according to the treatment method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 Women undergoing advanced infertility treatments experience repercussions on their physical, reproductive, and mental health of women at the same time increasing the economic burden for the whole family. 23 The diagnosis of infertility and its related social and economic experiences have serious repercussions on the physical, psychological, and social domains of a couple’s health. 24 The intensity of such influences is profound for female partners as some studies report 30–40% of the women with infertility difficulties meet the diagnostic criteria for psychiatric disorders including stress disorders, dysthymia, and major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%